Practices of contraception among rural people in Nellore district, Andhra Pradesh: a cross-sectional study - Gollapalli, Pavan Kumar; Conjeevaram, Jyothi; Veluri, Chandrasekhar (International Journal Of Community Medicine And Public Health, 2019)
Background: As per the census 2011, the provisional population of India is about population of 1.21 billion. It is now estimated that by 2030, India will most likely overtake China to become the most populous country on the earth. India was the first country in the world to officially launch a national family planning programme (NFPP) in 1952 to reduce birth rate and to stabilize the population at a level consistent with the requirement of national economy. Protecting the young couple from unwanted fertility and educating them to adopt their desired family through informed choice, are among the prerequisites to achieve a TFR of 2.1. To study the prevalence of contraceptive methods among rural population and to study the reasons for not using family planning methods among eligible couples. Methods: A community based cross-sectional study was done among 600 married women in reproductive age, in the three randomly selected Primary health centre areas, one each from the three revenue divisions of Nellore, dated from June 2011 to May 2012. Results: The contraception prevalence rate was 56.3% among whom 91.4% adopted permanent family planning methods. Conclusions: The contraceptive prevalence rate in the study subjects was 56% which was lower than that reported in NFHS-III (67%). Majority of the women opted for permanent sterilization when compared to spacing methods.